2023
DOI: 10.1108/jima-01-2023-0008
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of viewers’ watch behavior toward YouTube videos: evidence from the most populous Muslim-majority country

Abstract: Purpose This study aims to determine the impact of attitude toward content creators, subjective norm and perceived content quality in affecting people’s intention and behavior to watch videos posted on YouTube in Indonesia. Design/methodology/approach Using questionnaire, data from the total of 112 individuals living in Indonesia were gathered in this study, and these respondents are individuals who have been watching YouTube contents at least 3 h a day for the past eight months. Moreover, all of these data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 101 publications
0
0
0
Order By: Relevance
“…One of the strengths of TRA is its emphasis on the role of subjective attitudes and norms in determining behavior. Where attitude is a person's assessment of a behavior (Keni et al, 2024), while subjective norms according to Ajzen (1991) in Tobias-Mamina et al, (2023) refers to social pressure to do or not perform a behavior. Ajzen (1991) said Subjective Norms (SN) are variables related to social factors and refer to the extent to which the thoughts and opinions of people around affect products and services that are new alternatives .…”
Section: Theory Of Reasoned Action (Tam)mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the strengths of TRA is its emphasis on the role of subjective attitudes and norms in determining behavior. Where attitude is a person's assessment of a behavior (Keni et al, 2024), while subjective norms according to Ajzen (1991) in Tobias-Mamina et al, (2023) refers to social pressure to do or not perform a behavior. Ajzen (1991) said Subjective Norms (SN) are variables related to social factors and refer to the extent to which the thoughts and opinions of people around affect products and services that are new alternatives .…”
Section: Theory Of Reasoned Action (Tam)mentioning
confidence: 99%
“…Research Cahyono et al, (2024) and Burgess et al, (2023) It has been shown that TAM can be used to study user behavior in e-commerce, user convenience perceptions and usage attitudes. Research Keni et al, (2024) and Tobias-Mamina et al, (2023) has shown that TRA can be used to study user behavior in a variety of contexts, such as social media use and purchase intention and marketing strategies. However, there have been no studies that use a combination of these two theoretical models to study user behavior in using social media and live streaming features of TikTok and e-commerce platform Shopee.…”
Section: Introductionmentioning
confidence: 99%
“…This process involves a series of cognitive and emotional stages that have a significant impact on one's personal life or business endeavors (Arief et al, 2023;Wibisono & Keni, 2023). Meanwhile, within the world of business, the purchase decision is a critical factor that can determine whether or not companies or organizations can achieve success in the industry since this variable is linked directly with the level of sales that companies could generate regarding the product that they sold to consumers (Keni et al, 2023). In this case, when buyers or individuals buy their products, it will eventually increase the products' sales level, while on the contrary, when individuals decide against buying the companies' product, such decision will negatively affect the number of sales that companies can generate from the product (Gupta et al, 2022).…”
Section: Decision To Adoptmentioning
confidence: 99%
“…Theory of Reasoned Action (TRA) diterima secara luas sebagai sebuah konsep untuk menjelaskan green buying behavior konsumen yang dikemukakan oleh Fishbein dan Ajzen (1975). Mengacu pada teori tersebut, Keni et al (2023) berpendapat bahwa perilaku individu didasari oleh sikap terhadap perilaku tersebut, dimana sikap tersebut menunjukkan penilaian individu terhadap perilaku. Berkaitan dengan green buying behavior, Albayrak et al (2013) berpendapat bahwa sikap konsumen yang berkaitan dengan masalah lingkungan sangat menentukan intensi pembelian produk ramah lingkungan.…”
Section: Tinjauan Pustaka Theory Of Reasoned Actionunclassified
“…Berdasarkan teori tersebut, penelitian ini ingin mengkaji intensi pelanggan untuk menginap di green hotel ketika dipengaruhi oleh sikap pelanggan terhadap hotel tersebut. Keni et al (2023) menyimpulkan bahwa sikap tersebut didasari oleh penilaian individu terhadap perilaku, sehingga penelitian ini mengidentifikasi penilaian tersebut melalui variabel green brand knowledge, environmental knowledge, dan environmental concern.…”
Section: Tinjauan Pustaka Theory Of Reasoned Actionunclassified